Letter from the Editors in Chief - Armijos Guzmán, Juan Sebastián; Guamán, Flor (El Outsider: Journal of International Relations and Political Science, 2025)
The editors’ letter extends a special thank you to all our contributors, whether members of the Editorial Committee or Expert Reviewers. We hope you enjoy every article in this tenth edition.